A comparative evaluation of micro-leakage in fiber post luted and core buildup performed with two different resin cements: An In vitro study - Vijay S Kadam; Dayanand Huddar; Mokshada Badadare; Priyanka Jadhav; Sakshi Aher; Ayushi Botadra (Wolters Kluwer Medknow Publications, 2023)
Objective: To compare the micro-leakages of fiber post luted and core buildup performed with ParaCore (Coltene) and LuxaCore (DMG) resin cement. Materials and Methods: Thirty-six single-rooted teeth were selected and treated with root canal treatment and fiber post cementation with two types of resin cement (LuxaCore and ParaCore). Samples were exposed to 500 cycles of thermocycling, immersed in 2% methylene dye and centrifuged and sectioned longitudinally, and checked under a stereomicroscope. Results: LuxaCore and ParaCore showed a mean of 0.39250 mm and 0.47500 mm micro-leakage, respectively. Conclusion: There was a statistically non-significant difference seen with group 3 (LuxaCore) versus group 4 (ParaCore) (P > 0.05).